Cohort profile: targeted antenatal screening for haemoglobinopathies in Basel - Gabriela Amstad Bencaiova; Irene Hoesli; Franziska Geissler (BMJ Open)
Purpose The pregnancy cohort was established to examine the prevalence and variety of haemoglobinopathies in a high-risk group of pregnant women.Participants The pregnancy cohort is located in the Department of Obstetrics and Antenatal Care, University Hospital of Basel. The pregnant women were recruited in the first trimester between June 2015 and May 2019. Family origin questionnaires were used to screen pregnant women for the risk of a haemoglobin variant. Based on the questionnaire, pregnant women were divided into two groups: women with a high risk and women with a low risk of a haemoglobin variant. In women with a high risk, red blood cell indices, iron status and chromatography were conducted.Findings to date 1785 pregnant women were recruited. Out of the 1785 women, 929 were identified as a part of the high-risk group. Due to the missing data of 74 pregnant women with a high risk, the final analysis was conducted in the remaining 855 women. The prevalence of haemoglobinopathies in the high-risk group was 14.5% (124/855).Future plans This cohort will be used to: (1) implement the screening in prenatal care in Basel; (2) recommend the screening among pregnant women with a high risk of a haemoglobin variant in Switzerland; (3) improve prenatal and neonatal care in patients with a haemoglobin variant; (4) examine adverse pregnancy outcomes in women with a haemoglobin variant and (5) reduce maternal and neonatal morbidity and mortality in the future.Trial registration number ClinicalTrials.gov Registry (NCT04029142).